(untitled) (Revista Brasileira Multidisciplinar, 2013)
Educational processes, among them environmental education, are necessary to face the socioenvironmental problems in today’s world. Among all the pedagogical resources, games stand out for their playful nature, allowing to approach and assimilate contents, even the most complex ones, as a result of their funny characteristic. However, to overcome the models of educational practices based on ethnocentric, invasive way, it is necessary to consider a comprehensive educational concept which allows the construction of knowledge "with the subject" and not "for the subject". One way to overcome this model is linked to a participatory process involving the final users of the instrumental in its dynamic of construction, that is, a methodology which is able to include the subject in his/her knowledge process. So, this paper presents the focal groups as a resource in the construction of playful environmental education, presenting a report of a research experience in which the main theme was the perceptions of environmental, technological and social risks. In order to overcome a conception of a merely mechanicistic environmental education, we offer a contribution to the debate on the participative methodologies in social research, discussing the focal groups in the process of elaboration of a ludic instrument, polissemic and collectively built, which has resulted in the construction of a game with a double nature in its social construction of knowledge, being the first one, the process of game elaboration itself and the second, the catalyser character of debates, allowing the social construction of knowledge in the confluence of the multiple subjectivities involved in the practical application of the dynamics.